Faith and Freedom: Life of Harriett N. K. Jones, 1825-1903 - Connie Jones Pillsbury (Symphony in the Flint Hills, 2011)
From Harriett’s diary: These gardens of the desert I have gazed upon them all—enraptured until my eyes, dilated with the sight, have taken in the “encircling vastness.” When Harriet N.K. Jones arrived in Kansas in October of 1855 to join her missionary husband, Harvey Jones, she brought with her a lifetime of faith, training and discipline.
Keywords: Harriet N.K Jones; Muskingum; River; Ohio; Choctaw; faith; bible; Church of Christ; Wabunsee; Oberlin